1994
DOI: 10.1177/019459989411000202
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of facial, cochlear, and other nerve functions in acoustic neuroma treatment

Abstract: Between March 1966 and September 1992, 1400 acoustic neuromas were treated in Paris, France, by surgical excision. The findings over the last 7 years are presented. The translabyrinthine approach has been used in more than 85% of cases. Where hearing preservation is attempted, the middle fossa approach has been adapted for intracanilicular tumors and the retrosigmoid approach for small tumors extending into the cerebellopontine angle, in which the fundus of the internal meatus is free of tumor. The main goal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(65 citation statements)
references
References 16 publications
6
57
0
1
Order By: Relevance
“…Since the first successful resection of a VS occurred in 1894 2 , surgical techniques have been continuously refined to reduce patient morbidity and mortality rates 3,4 . over the last century, treatment of VS has undergone immense changes and the focus of surgery has improved from prolongation of patient's life towards preservation of cranial nerve function 5 , specially the seventh nerve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first successful resection of a VS occurred in 1894 2 , surgical techniques have been continuously refined to reduce patient morbidity and mortality rates 3,4 . over the last century, treatment of VS has undergone immense changes and the focus of surgery has improved from prolongation of patient's life towards preservation of cranial nerve function 5 , specially the seventh nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Harvey cushing improved surgical techniques and brought the mortality rate down to approximately 20% 3 performing sub-total removal of the tumors. Improvement in surgical techniques and development of new technological devices had brought the mortality rate to under 2% 4,5 . The advances and improvements in microsurgical techniques have changed the actual goals of surgery, being facial nerve preservation an utmost concern 3 .…”
Section: Dra Rafaela Júlia Batista Veronezi -Rua Santaré� Qd 235 Lt mentioning
confidence: 99%
“…Other studies have corroborated this inverse relationship between the size of the tumor and preservation of the facial nerve function [20]. With continuous intraoperative monitoring of the facial nerve, however, Sterkers et al [21] reported that the percentage of preserved facial function (grade I or II) improved from 20 to 52% for large tumors (1 3 cm), from 42 to 81% for medium tumors (2-3 cm in diameter) and from 70 to 92% for small tumors (!2 cm in diameter). These results demonstrate the challenge for preservation of facial nerve function during resection of the acoustic neuroma and illustrate the need for techniques for treatment that will preserve function.…”
Section: Surgerymentioning
confidence: 90%
“…Hearing was not preserved in that series in any of the 3 patients with large tumors in whom hearing preservation was attempted. Sterkers et al [21] report that hearing was preserved in 38.2% of cases Williams operated on by means of the retrosigmoid route and 36.4% of cases after the middle fossa approach. Cerullo et al [23] showed that, for the 64 patients with functional preoperative hearing, 13 patients retained hearing postoperatively: 5 had normal hearing (PTA !…”
Section: Surgerymentioning
confidence: 99%
“…[1,2,11,[14][15][16][17]19] Given the medical, psychological, and functional sequelae of facial nerve weakness, [13,23] close attention has been paid to factors that influence facial nerve outcome, and a number of authors have reported on their experience with these complex tumors. [1,11,17,18,21] In recent years, the phenomenon of delayed facial nerve palsy has become evident. [10,12,22] This condition, characterized by spontaneous deterioration of facial nerve function in a patient who has otherwise normal or near-normal facial function in the immediate postoperative period, has been reported to occur in 15 to 29% of patients who underwent microsurgical resection of vestibular schwannomas.…”
mentioning
confidence: 99%